Tax authority advice and the public - Daly, Stephen, 1989- (Oxford, UK ; Hart Publishing, 2020)
"There is now almost universal acceptance that tax law is overly complex and indeterminate; and yet, there has to date been no comprehensive assessment of the role of the tax authority in the current arrangement. If the legislation and case law offer few immediate answers to the taxpayer, then the role of Her Majesty's Revenue & Customs (HMRC) in advising taxpayers becomes more apparent. This monograph contends that the provision of advice by HMRC is desirable by virtue of the rule of law and it follows that any such advice should be correct, clear, accessible and reliable. Additionally, there should exist some means of scrutinising the advice in order to check that it satisfies these criteria. Tax Authority Advice and the Public explores this view of HMRC's role in tax collection. It explains the deficiencies in the current system in this light, highlighting the pitfalls for taxpayers and practitioners as well as the potential remedies. Finally, the book assesses potential reforms which could be adopted in order to alleviate existing problems. A timely and ambitious work, this book is essential reading for practitioners and academics interested in the interaction between tax administration and public law"--
Introduction -- What is HMRC Advice? -- The Role of HMRC Advice -- Problems with Advice -- Scrutiny -- Remedies -- Reforms -- Conclusion.
Based on author's thesis (doctoral - University of Oxford, 2017) issued under title: HMRC and the public : the case for reform of soft law.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on online resource; title from digital title page (viewed on May 01, 2020).
Keywords: Great Britain. -- HM Revenue & Customs; Tax administration and procedure -- Great Britain; Advisory opinions -- Great Britain; Soft law -- Great Britain; Taxation & duties law; Electronic books